Preaged remodeling of myofibrillar cytoarchitecture in skeletal muscle expressing R349P mutant desmin - Diermeier, Stefanie; Buttgereit, Andreas; Schürmann, Sebastian; Winter, Lilli; Xu, Hongyang; Murphy, Robyn M.; Clemen, Christoph S.; Schröder, Rolf; Friedrich, Oliver (Neurobiology of Aging, 2017)
The majority of hereditary and acquired myopathies are clinically characterized by progressive muscle weakness. We hypothesized that ongoing derangement of skeletal muscle cytoarchitecture at the single fiber level may precede and be responsible for the progressive muscle weakness. Here, we analyzed the effects of aging in wild-type (wt) and heterozygous (het) and homozygous (hom) R349P desmin knock-in mice. The latter harbor the ortholog of the most frequently encountered human R350P desmin missense mutation. We quantitatively analyzed the subcellular cytoarchitecture of fast- and slow-twitch muscles from young, intermediate, and aged wt as well as desminopathy mice. We recorded multiphoton second harmonic generation and nuclear fluorescence signals in single muscle fibers to compare aging-related effects in all genotypes. The analysis of wt mice revealed that the myofibrillar cytoarchitecture remained stable with aging in fast-twitch muscles, whereas slow-twitch muscle fibers displayed structural derangements during aging. In contrast, the myofibrillar cytoarchitecture and nuclear density were severely compromised in fast- and slow-twitch muscle fibers of hom R349P desmin mice at all ages. Het mice only showed a clear degradation in their fiber structure in fast-twitch muscles from the adult to the presenescent age bin. Our study documents distinct signs of normal and R349P mutant desmin-related remodeling of the 3D myofibrillar architecture during aging, which provides a structural basis for the progressive muscle weakness.
EVALuna2:7375